Observing logics: revisiting reason in The Brothers Karamazov - Kim, Eric (Studies in East European thought, 2025)
Very often in frameworks for and presentations of The Brothers Karamazov , the modern reading public attempts to divide characters by their ability to reason. Usually Ivan is remembered for his reason, pitted against Dmitri’s passion. Adapting some terminology from mathematical logic, I propose and trace a different approach to reason in Dostoevsky’s text, to recast its canonical characters into alternative, though still fluid, categories. This exercise aims not to reinscribe or to reinterpret Dostoevsky’s novel but rather to reconsider an aspect of reasoning, specifically modes or forms of logic. With an admittedly imperfect mapping of characters onto these logical structures, this article encourages the ways in which we can trouble notions of stable reason and sound logic as they operate in the novel.